Investigating the Impact of a Musical Intervention on Preschool Children’s Executive Function - Bowmer, Alice; Mason, Kathryn; Knight, Julian; Welch, Graham (Frontiers in Psychology, 2018)
The impact of music interventions on the cognitive skills of young children has become the focus of a growing number of research studies in recent years. This study investigated the effect of weekly musicianship training on the executive function abilities of 3-to-4-year-old children at a London, UK preschool, using a two-phase experimental design. In Phase 1, fourteen children (Group A) took part in eight weekly musicianship classes, provided by a specialist music teacher, whilst twenty-five children (Groups B and C combined) engaged in nursery free play. Results of this Phase showed Group A to have significantly improved on two measures relating to planning and inhibition skills. During Phase 2, Group A continued with music classes, whilst Group B began music classes for the first time and Group C took part in an art intervention. Repeated measures ANOVA found no significant difference in performance improvement between the three participant groups during phase 2; however, the performance difference between groups was nearing significance for the peg tapping task (p=.06). The findings from this study contribute to current debates about the potential cognitive benefit of musical interventions, including important issues regarding intervention duration, experimental design, target age groups, executive function testing and task novelty.